S3 Dorsal Root Ganglion/Nerve Root Stimulation for Refractory Postsurgical Perineal Pain: Technical Aspects of Anchorless Sacral Transforaminal Lead Placement - X. Zuidema; J. Breel; F. Wille (Case Reports in Neurological Medicine)
Chronic perineal pain limits patients in physical and sexual activities, leading to social and psychological distress. In most cases, this pain develops after surgery in the urogenital area or as a consequence of trauma. Neuromodulation is one of the options in chronic postsurgical perineal pain treatment. We present a case of refractory perineal pain after right sided surgical resection of a Bartholin’s cyst which was treated with third sacral nerve root/dorsal root ganglion stimulation using the transforaminal approach. We describe a new anchorless lead placement technique using a unique curved lead delivery sheath. We postulate that this new posterior foraminal technique of lead placement is simple, safe, and reversible and may lower the occurrence of lead related complications.